Sustainable entrepreneurship: a literature review - Rosário, Albérico Travassos (2022)
These days, issues such as environmental degradation, the wealth gap, and unequal access to opportunities and resources are increasing. These concerns have increased the need for sustainable entrepreneurship, defined as sustainable business practices. Entrepreneurship is central in transitioning towards a more sustainable future, whereas aligning the social, economic, and ecological objectives and ecological entrepreneurs plays a role. This scoping literature review analyzes the field of sustainable entrepreneurship and the extent of the holistic integration in the global business arena, therefore filling a gap in the existing literature. It aims to analyze the depth of existing pieces of literature on sustainable entrepreneurship, its definitions, and its applications in business practices. The analysis relies upon a literature search on the SCOPUS database around the keywords ‘Sustainability’ and ‘Sustainable Entrepreneurship’. The scientific software VOSviewer is used to better illustrate the linkage of major categories and correspondent trends, related with both business growth and maintenance of ecological systems. It concludes that the desired levels of sustainability require collaborations between all stakeholders, while the transition towards service-oriented business models has contributed to the growth of sustainable entrepreneurship. Nevertheless, existing institutional structures favor current unsustainable businesses and systems over the newer sustainable ones, demanding ecopreneurs to initiate institutional changes.